Ensino de Ciências: um estudo no 6º ano do ensino fundamental com enfoque nas práticas pedagógicas sobre o meio ambiente - Gonzaga, Adana Teixeira (2020)
The research entitled SCIENCE TEACHING: A STUDY IN THE 6th YEAR OF ELEMENTARY SCHOOL WITH A FOCUS ON PEDAGOGICAL PRACTICES ON THE ENVIRONMENT aimed to analyze the limits, challenges and possibilities of the pedagogical practice of Science Teaching, focusing on the environment, in the 6th year of Elementary School. The issues that involve pedagogical practice in science teaching, have undergone changes in the midst of educational actions, however they are still developed in a traditional way in the school context, which may or may not affect the education of students regarding scientific concepts. In this sense, it is necessary to understand how pedagogical practices, with a focus on the environment, are developed and mainly what teachers report on the development of their teaching work. For the dialogue to take place we start from some categories of analysis that are: Science Teaching, pedagogical practice and environment. In the methodological procedures we work on a qualitative research approach. The type of research presented is descriptive, with the observation techniques of pedagogical practices developed in the classroom in the discipline of natural sciences and semi-structured interviews with the professor of the discipline. In the analysis of the data we work from Laurence Bardin with the analysis of the content going through the description of what was observed and said in the research process. The results found after the analysis showed us limits that show situations related to the working conditions that correlate with the time of the disciplines, physical space, number of students per room, the workloads, use of the textbook, among others. From these limits, we find the challenges that move along the paths of initial and continuing formation. Finally, we found ourselves with the possibilities of changing this scenario involving pedagogical tutorials, which seek to expand the reading and construction of interdisciplinary concepts in science teaching, the defense and effort in the construction of public policy for teacher education. We conclude that the pedagogical practices in science teaching present challenges, limits, however they also build possibilities in their daily lives that directly influence the pedagogical training of teachers and contribute to the academic education of students with a focus on the environment, these bases demand an impulse for a more critical, reflective, collective way of thinking aiming the changing of the world.